2019
DOI: 10.1186/s12906-019-2645-y
|View full text |Cite
|
Sign up to set email alerts
|

Topical hydrogel containing Fumaria vaillantii Loisel. extract enhances wound healing in rats

Abstract: Background Fumaria species (Fumariacea) has traditionally been used in wound healing in Iranian folk medicine. However, with the discovery of newer agents, its use has faded off into total obscurity. This study explored the wound healing potential of a gel containing 10% Fumaria vaillantii Loisel through topical application of total extract in a model of excisional as well as incisional wound healing in albino Wistar rats. Methods Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…They contained alkaloids from three classes, i.e., protopine, protoberberine, and phenanthridine derivatives, and their content was several times higher than in the aerial parts ( Table 1 ). Previous studies of this species have shown the presence of several classes of isoquinoline alkaloids such as benzylisoquinoline, spirobenzylisoquinoline, phthalideisoquinoline, morphinandiene, protoberberine, protopine, and benzophenanthridine derivatives [ 15 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ], as well as quercetin [ 29 ]. In addition, several other classes of phytochemicals were detected using obsolete unspecific methods [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…They contained alkaloids from three classes, i.e., protopine, protoberberine, and phenanthridine derivatives, and their content was several times higher than in the aerial parts ( Table 1 ). Previous studies of this species have shown the presence of several classes of isoquinoline alkaloids such as benzylisoquinoline, spirobenzylisoquinoline, phthalideisoquinoline, morphinandiene, protoberberine, protopine, and benzophenanthridine derivatives [ 15 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ], as well as quercetin [ 29 ]. In addition, several other classes of phytochemicals were detected using obsolete unspecific methods [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gels have several advantages in promoting wound healing; among them we can mention its ability to provide the humid environment required for healing, in addition to allowing the incorporation of plant extracts. [34][35][36]…”
Section: Discussionmentioning
confidence: 99%
“…Roodbordei et al investigated topical hydrogel containing Fumaria vaillantii Loisel. extract enhances wound healing in rats [11]. The topical effect of grape seed extract 2% cream on surgery wound improves cellular structure and wound contraction as investigated by Hemmati et al [1].…”
Section: Discussionmentioning
confidence: 99%